The role of digital media in motivating teenage pregnancy prevention among teenagers in Ghana - Abdul Malik, Karamatu (My University, 2025)
This thesis investigates the role of digital media in shaping knowledge, information-seeking behaviors, and preventive health actions related to teenage pregnancy among adolescents in Ghana. With the growing reliance on digital platforms for sexual and reproductive health information, this study examines how digital media influence adolescent engagement with pregnancy prevention in a context where cultural stigma and limited access to services persist. Grounded in Protection Motivation Theory (PMT) (Rogers, 1983), the research evaluates the effects of perceived severity, vulnerability, response efficacy, self-efficacy, and response costs on pregnancy-related knowledge, digital media engagement, online health information-seeking, and preventive behaviors. Additional variables include demographic characteristics and media-related factors that shape adolescent reproductive health decisions. A quantitative cross-sectional survey was conducted with adolescents aged 18–19 (n = 429). Descriptive statistics, including means, standard deviations, and Cronbach’s [alpha], were computed to assess reliability of the constructs. Correlation and hierarchical regression analyses were performed to test the hypotheses and answer the research questions. Findings indicate that self-efficacy ([beta] = .337, t = 4.01, p < .001) and response costs ([beta] = .235, t = 3.26, p < .01) significantly predicted digital media engagement, while perceived severity ([beta] = –.303, t = –3.48, p < .01) was negatively associated. Protective behaviors were significantly predicted by response efficacy ([beta] = .324, t = 5.30, p < .001), self-efficacy ([beta] = .166, t = 2.62, p < .05), online information-seeking ([beta] = .305, t = 5.45, p < .001), and digital media use ([beta] = .087, t = 2.63, p < .05). Correlation analyses further confirmed strong positive relationships between online health information-seeking, response efficacy (r = .769, p < .001), and self-efficacy (r = .792, p < .001). Regression models explained significant variance across outcomes, demonstrating that efficacy beliefs and digital engagement, rather than threat perceptions, are key drivers of preventive behavior. These findings underscore the explanatory power of PMT while extending it into a digital health context. This study highlights the potential of digital media to serve as an effective platform for motivating adolescent pregnancy prevention in Ghana. It emphasizes the importance of designing culturally relevant, accessible, and empowering digital interventions that build self-efficacy, enhance trust in digital health tools, and address barriers that limit sustained engagement.
Keywords: Teenage pregnancy; Prevention; Motivation; Digital media; Self-efficacy; Health information seeking behavior